Bài 7. Lập phương của một tổng. Lập phương của một hiệu

H24

Chứng minh \({\left( {a - b} \right)^3} =  - {\left( {b - a} \right)^3}\) 

HM
12 tháng 1 2024 lúc 21:40

\(\begin{array}{l}{\left( {a - b} \right)^3} = {a^3} - 3{a^2}b + 3a{b^2} - {b^3}\\ - {\left( {b - a} \right)^3} =  - \left( {{b^3} - 3{b^2}a + 3b{a^2} - {a^3}} \right) = {a^3} - 3{a^2}b + 3a{b^2} - {b^3}\end{array}\)

Vậy \({\left( {a - b} \right)^3} =  - {\left( {b - a} \right)^3}\) (đpcm).

Bình luận (0)

Các câu hỏi tương tự
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
QL
Xem chi tiết
H24
Xem chi tiết